160 ps Yb:YAG/Cr:YAG microchip laser. (21st August 2018) - Guo, Xiaoyang; Hamamoto, Koichi; Tokita, Shigeki; Kawanaka, Junji
Abstract: By cryogenically cooling the Yb:YAG/Cr:YAG medium, one can break through the damage limit of Yb:YAG/Cr:YAG passively Q-switched microchip lasers at room temperature and thus achieve a shorter minimum pulse duration. In the proof of principle experiment we carried out, a 160.6 ps pulse duration was obtained. To the best of our knowledge, this is the first realization of sub-200 ps pulse operation for an Yb:YAG/Cr:YAG microchip laser.